Effectiveness and Safety of Targeted Agents Combined With Chemoradiotherapy for the Treatment of Esophageal Cancer: A Network Meta-Analysis - Liu, Peng; Wang, Guo-Fei; Peng, Hua; Zhang, Lei; Li, Xiao-Yan; Zeng, Qiao-Miao; Li, Qian; Zhou, Jian-Hui (Frontiers in Oncology, 2021)
Background Concurrent chemoradiotherapy (CRT) is the preferred treatment strategy for inoperable esophageal cancer (EC). However, the effect of CRT needs to be improved. Methods This study comprehensively analyzed targeted agents combined with CRT for the treatment of EC by a network meta-analysis. The search was performed in public databases from incipient to 5 August 2021. Randomized controlled trials comparing the effect of targeted agents combined with CRT and CRT alone on EC patients were included. Results Ten studies were included. For progression-free survival (PFS), nivolumab (67.4%) and erlotinib (64.6%) had advantages based on Cox analysis. Regarding the frequency of PFS, cetuximab (OR: 1.39; 95% CI: 1.01, 1.91; p=0.042) and nivolumab (OR: 1.81; 95% CI: 1.34, 2.44; p<0.01) were significantly superior to the control. For overall survival (OS), nivolumab (71.6%) in Cox analysis and nimotuzumab (69.7%) in frequency analysis were found to have relative advantages. Nimotuzumab combined with CRT was significantly better than the control with regard to endoscopic and the pathologic complete response (epCR; OR: 2.81; 95% CI: 1.28, 6.14; p=0.011) and objective response rate (ORR; 4.71; 95% CI: 1.45, 15.29; p=0.008). The targeted drugs were not associated with significant SEA risk. Conclusion In conclusion, compared to CRT alone, cetuximab and nivolumab combined with CRT were found to significantly improve the PFS rate only based on the frequency results. However, there was no benefit in terms of OS. For epCR and ORR, nimotuzumab was better than the blank control. Considering the limitations in this study, more well-designed RCTs are needed in the future to validate the results.